A luta pela terra na (contra) mão da ordem capitalista : uma leitura a partir da luta pela terra do MST no município de Petrolina/PE - Sousa, Ronilson Barboza de (2014)
This thesis aims to analyze the condition of the land struggle in the fight against capital, from the reality of the Landless Rural Workers Movement (MST) in the city of Petrolina -PE. The reflective analytical reading centered on the method of dialectical materialism, which allowed to understand how capital expands through its territorial and monopolization of the territory, resulting in social conflicts. In the case of the city Petrolina -PE, the expansion of capitalist relations was made possible mainly by the concentration of power of the ¡°Coelho¡± family and its strong national and international networking. The path chosen by the ruling class to advance the capital was, primarily, use the paid labor force, through control of the lands and waters of the Sao Francisco River. The activity of irrigated fruit gave the city of Petrolina status of one of the most important hubs for agribusiness in the circuit of capital promoting the expropriation of peasant production unit, boosting labor mobility and forming a relative surplus population in the city, hence various conflicts. At the current stage of capital accumulation, in the pursuit of profit obtaining, their demands clash with the demands of the workers. The participation of the state, through public policy was and remains essential to mediate these tensions and ensure the continued reproduction of the capital. The capital is incapable of yielding the minimum needs of human achievements. Moreover, although the MST has advanced in the fight, without breaking the rule of capital, through the occupation of unproductive latifundia, ends becoming functional to this, either as an extension of manufacturing, or through food production, it lowers the cost of reproduction of labor power. At MST.s camps and settlements, the capital monopolizes territory, subjecting the land of work and life in the land of business: merchandise, leaving them only to work for capital, particularly in agribusiness. Thus, it is evident that the struggle for land, agrarian reform collides with the capitalist order in progress, becoming an anti-capitalist struggle, even if not all the fighting have full conviction of that process.